DINAMIKA KUALITAS UDARA AMBIEN SELAMA MASA PANDEMI COVID-19 DI KAWASAN INDONESIA TOURISM DEVELOPMENT CORPORATION NUSA DUA BALI - Sulistiani, Ika; Partama, I GD Yudha; Kaler Surata, Sang Putu; Sumantra, I Ketut (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 15 No 1 (2021), 2021)
The Covid-19 pandemic has increased the improvement of air quality in various countries in the world, such as China, Italy, New York, India, Spain and Korea. This study aims to compare ambient air quality during the Covid-19 pandemic with new normal and normal periods, assess the effect of meteorological factors on ambient air quality, and map the spatial distribution of ambient air quality during the normal, Covid-19 pandemic and new normal in the ITDC Nusa Dua area. Air concentration parameter data and meteorological factors were collected using the midget impinger and direct reading method in 2019 (normal period), March and May 2020 (Covid-19 pandemic period) and July, September, and November 2020 (new normal period). Furthermore, comparing air quality using the Anova test, assessing the effect of meteorological factors on air quality using a linear regression test, and mapping the distribution of ambient air using the ArcGis 10.8 application. The analysis showed that the air quality during the Covid-19 pandemic and the new normal was significantly different from the normal period. The concentrations of SO2, NO2, NH3, CO, TSP and H2S during the Covid-19 pandemic and normal just decreased while the O3 concentration increased compared to the normal period. The meteorological factor that affects air quality is the wind speed, the higher the wind speed the lower the O3 concentration. Map of the distribution of spatial concentrations of SO2, NO2, NH3, CO, O3 and H2S in the normal, Covid-19 pandemic and new normal, lowest at the coast point of the peninsula and the highest distribution at the ITDC roundabout, bima statue or influence TSP is the highest spatial concentration of normal distribution at the ITDC roundabout and the bima statue, while the Covid-19 pandemic and normal are only at the coast point of the peninsula beach. Keywords: ambient air quality; Covid-19; pandemic; tourism.